South African Astronomical Observatory data archiving for multi-wavelength astronomy research - Botha, Lucian (Department of Computer Science, 2024)
This research investigates the best practices for creating a data archive system that can store optical and radio astronomy data as well as interact with other astronomy archives. Archives are built and maintained by staff that specialise in big data storage, information security, database administration, and general information technology that provide platforms for access to research data to the broader astronomy community. The tools and services provided by the IVOA allow data to be located, compared, and retrieved, combining multispectral and multiple instrument data from different archives to show the evolution of data interoperability across wavelengths. The diverse methods applied and the organisation of resources and collaboration between different facilities to reach common goals will broaden the scope and availability of data throughout the research community. Using data from various archives makes multi-wavelength investigations a significant topic in astronomy. Astronomy data archives employ a variety of authentication mechanisms, including Open Authorization (OAuth), Security Assertion Markup Language (SAML), Central Authentication Service (CAS), and traditional web-based authentication with usernames and passwords. Challenges faced by archives include the increased complexity of data which can be addressed by choosing the appropriate level of standardisation. As astronomy and data science are rapidly evolving, it is a challenge to keep up with all of the new developments, so there needs to be a strategy of research and development so that new technologies and techniques can be adopted.